Peningkatan Pembangunan Ekonomi Untuk Kualitas Hidup Manusia Di Daerah Istimewa Yogyakarta - Fauzuna Naufal Wijanarko; Rini Dwi Susanti (MBIA, 2023)
This study aims to analyze economic development towards improving the quality of human life in the Special Region of Yogyakarta from 2013 to 2019. Theoretically, the Human Development Index (IPM) measures human resources and is used as a standard indicator of human welfare. The HDI indicator is based on the quality of health, education and people's purchasing power. An increase in the HDI value indicates that there has been an increase in human welfare and rate in an area. Human Development Index (IPM) is the dependent variable, while capital expenditure, poverty, Regional Minimum Wage (UMP), and Gross Regional Domestic Product (GRDP) are independent variables. The research approach uses a fixed effect model: panel data. Partial research results show that capital expenditure has a positive but not significant effect on HDI, while poverty has a negative and insignificant influence on HDI. In addition, UMP and GRDP have a significant positive impact on HDI. Simultaneously, poverty, capital expenditure, UMP and GRDP substantially influence the HDI in the Special Region of Yogyakarta. Keywords: Human Development Index, Poverty, Provincial Minimum Wage, Government Expenditure, Gross Regional Domestic Product. Abstrak Penelitian ini bertujuan menganalisis pembangunan ekonomi terhadap peningkatan kualitas hidup manusia di Daerah Istimewa Yogyakarta pada tahun 2013-2019. Secara teoritis, Indeks Pembangunan Manusia (IPM) merupakan metode pengukuran sumber daya manusia yang dijadikan standar indikator kesejahteraan manusia. Indikator IPM didasarkan pada kualitas kesehatan, pendidikan dan daya beli masyarakat. Meningkatnya nilai IPM menujukkan bahwa terjadi peningkatan kesejahteraan dan kualitas manusia di suatu wikayah. Indeks Pembangunan Manusia (IPM) sebagai variabel dependen, sedangkan belanja modal, kemiskinan, Upah Minimum Regional (UMP), Produk Domestik Regional Bruto (PDRB) sebagai variabel independen Pendekatan penelitian menggunakan fixed effect model yang bersifat data panel. Hasil penelitian secara partial menunjukan bahwa belanja modal berpengaruh positif tetapi tidak signifikan terhadap IPM, sedangkan kemiskinan berpengaruh negatif dan tidak signifikan terhadap IPM. Selain itu, UMP dan PDRB memiliki dampak positif yang signifikan terhadap IPM. Secara simultan, kemiskinan, belanja modal, UMP dan PDRB memiliki pengaruh signifikan terhadap IPM di Daerah Istimewa Yogyakarta. Kata Kunci: Indeks Pembangunan Manusia, Kemiskinan, Belanja Modal, Produk Domestik Regional Bruto, Upah Minimum Provinsi.